Anion Selective Disruption of Strong Intramolecular –NH⋅⋅⋅O=C Hydrogen Bonds in a Nonchromogenic Tripodal Benzoylthiourea Receptor to Display Colorimetric Response. Issue 14 (10th April 2019) - Dey, Sandeep Kumar; Hernández, Beatriz Gil; D'Souza, Milagrina; Mhaldar, Shashank N.; Gobre, Vivekanand V.; Dhuri, Sunder N.
Abstract: Tris(2‐aminoethyl)amine based tripodal benzoylthiourea receptor (L ) showed colorimetric response for fluoride and acetate in aprotic solvents within a range of competitive anions studied. The strong intramolecular –NH⋅⋅⋅O=C hydrogen bonding in the C3 symmetric receptor was not disrupted upon addition of any other anions except for fluoride and acetate as confirmed by 1 H‐NMR experiments in DMSO‐ d6 . The cavity of the tripodal receptor is locked due to the inward orientation of the intramolecular hydrogen bonded donor‐acceptor groups as confirmed by single crystal X‐ray crystallography. Fluoride and acetate could selectively disrupt the intramolecular –NH⋅⋅⋅O=C hydrogen bonds to establish intermolecular hydrogen bonds with both the –NH protons from each receptor side arm and showed visual colour change from colourless to yellow. However, hydrogen bonding observed in the solution state does not provide sufficient stabilization to the receptor fluoride/acetate complexes to be crystallized in the solid state and the receptor crystallised as solvates both from DMSO and THF in the presence of excess fluoride/acetate. From UV‐vis and 1 H‐NMR experiments, it was confirmed that the colorimetric sensing by the nonchromogenic benzoylthiourea receptor is due to strong hydrogen bonding between thiourea –NH groups and fluoride/acetate. Abstract : A tripodal benzoylthiourea receptor having strong intramolecular N−H⋅⋅⋅O=C hydrogen bonds between each receptor side arm showed colorimetric response for fluoride and acetate in aprotic solvents due to strong N−H⋅⋅⋅Anion hydrogen bond formation via disruption of N−H⋅⋅⋅O=C hydrogen bonds as confirmed by 1 H‐NMR and UV‐vis experiments.